Things We Do for No Reason™: Ova and Parasite Testing in Patients With Acute Diarrhea Arising During Hospitalization. Issue 4 (17th March 2021) - Golfeyz, Shmuel; Haviland, Adam; Burger, Alfred
Abstract : Inspired by the ABIM Foundation's Choosing Wisely ® campaign, the "Things We Do for No Reason ™ " (TWDFNR) series reviews practices that have become common parts of hospital care but may provide little value to our patients. Practices reviewed in the TWDFNR series do not represent clear‐cut conclusions or clinical practice standards but are meant as a starting place for research and active discussions among hospitalists and patients. We invite you to be part of that discussion . Abstract :